Bridging the gap: An exploratory study of corporate social responsibility among SMEs in Singapore - LEE, Mui Hean (Institutional Knowledge at Singapore Management University, 2012)
Corporate social responsibility (CSR) among small-medium enterprises (SME) is an overlookedarea, despite the latter’s emerging prominence as an economic player. To provide a comprehensiveanalysis of the CSR landscape among Singapore SMEs, a triangulation of 15 in-depth interviews anda self-administered Web survey was conducted among 113 senior executives from top 500 SingaporeSMEs (27.2% response). Key findings include (a) moderate awareness but low comprehension ofCSR; (b) engagement relevance to immediate stakeholders; (c) individual values, stakeholderrelationships, and governmental influences as main drivers; and (d) lack of various resources askey barriers. Implications and future research directions are discussed.